Characterizing the Real-Time Communication Performance of Virtual PLC in Industrial Edge Platform - Massimiliano Gaffurini; Dennis Brandao; Stefano Rinaldi; Alessandra Flammini; Emiliano Sisinni; Paolo Ferrari (IEEE Open Journal of Instrumentation and Measurement)
The integration of virtual programmable logic controllers (vPLCs) into industrial automation systems introduces the potential for enhanced maintainability and scalability through container-based automation. Unlike traditional hardware-based PLCs, vPLCs operate within edge computing environments, leveraging lightweight virtualization to provide flexibility and support modern microservices architectures. However, the open question is: can vPLCs meet the stringent real-time performance requirements of industrial control applications, particularly in communication with sensors and actuators? This article objective is to fill this gap. Differently from other works in the literature, the performance of the real-time data exchange between vPLCs and sensors/actuators is evaluated. In particular, this article presents and describes a methodology designed for comparing real PLC and vPLC in real-time industrial automation scenarios. The methodology includes the definition of specific performance metrics, the design of a standardized experimental setup to characterize both device real-time performance and uncertainty sources, and the development of analytical models to support simulations and digital twin applications. The proposed method of comparison is demonstrated in a reference use case, including real-time Ethernet connectivity; results lead to: 1) important conclusions about methodology effectiveness and 2) the analytical model of the considered use case. In detail, the analysis indicates that vPLCs exhibit approximately 50% higher jitter, suggesting a minimum recommended PROFINET cycle time of 2 ms for optimal performance. The findings contribute to the broader understanding of vPLC capabilities in industrial automation, offering practical insights for industries aiming to transition to modern, containerized control systems without compromising real-time communication performance.